Fascism and the classics: ideological manipulation and targeted translations of the Aeneid. (8th July 2022) - Scafoglio, Giampiero
Abstract: A major aspect of Fascist manipulation of classical culture is the tendentious practice of translating texts in order to emphasize the points apparently consistent with the regime's ideology: this process goes so far as to distort the meaning of the texts, which are used as means of political propaganda. This happened to the Aeneid, the most translated and probably the most misinterpreted poem in Italy during the Fascist period. I outline an overview of the translations made by Giuseppe Albini (1921 ), Francesco Vivona (1926 ), Giuseppe Lipparini (1928 ), Emilio Pratellesi (1930 ), and Guido Vitali (1930 ). I describe and illustrate with some examples the criteria followed by each author, with respect to lexical choice, sentence structure, and stylistic devices. Thus, I show how these translations (with the sole exception of that by Albini) are enslaved to their political purpose and betray the deep and complex message of the poem.